2015
DOI: 10.1159/000441645
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Abnormalities in Embryonic and Somatic Stem Cells

Abstract: The potential use of stem cells (SCs) for tissue engineering, regenerative medicine, disease modeling, toxicological studies, drug delivery, and as in vitro model for the study of basic developmental processes implies large-scale in vitro culture. Here, after a brief description of the main techniques used for karyotype analysis, we will give a detailed overview of the chromosome abnormalities described in pluripotent (embryonic and induced pluripotent SCs) and somatic SCs, and the possible causes of their ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 134 publications
(121 reference statements)
2
31
0
Order By: Relevance
“…In this study, no clonal chromosomal aberrations were identified in hTMSCs cultured in SFXFM. The results resemble those of previous studies [ 11 , 31 ], implying that supplement origin does not play a role in the maintenance of genome stability [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, no clonal chromosomal aberrations were identified in hTMSCs cultured in SFXFM. The results resemble those of previous studies [ 11 , 31 ], implying that supplement origin does not play a role in the maintenance of genome stability [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, some studies observed spontaneous numerical and structural chromosome aberrations within 10 passages of in vitro culture [ 28 , 29 ]. The specific in vitro environmental conditions would be a major factor influencing the conservation of genome integrity during culture [ 30 ]. In this study, no clonal chromosomal aberrations were identified in hTMSCs cultured in SFXFM.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested that senescent cells are unlikely to undergo malignant transformation, even if the presence of few tumorigenic cells can not be excluded[ 40 ]. The inconsistencies may be caused by tissue sources, culture conditions, culture times, and cuture passages[ 41 ]. Nevertheless, it is of critical importance to evaluate MSC genetic stability before clinical application.…”
Section: Characteristics and Functional Changes Of Aged Mscsmentioning
confidence: 99%
“…Further, the variation in the frequency of chromosomal abnormalities is a major incident involving most stem cell cultures, especially in somatic stem cells in which the aberration ranges from 10-15% of investigated cells in human hematopoietic stem cells and 15-20% in human bone marrow-derived MSCs (hBM-MSCs) (20). Based on numerous reports, adult stem cells establish various chromosomal abnormalities within the 10 passages of in vitro expansion, however, independent laboratories have reported contrasting results in this regard (20).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the variation in the frequency of chromosomal abnormalities is a major incident involving most stem cell cultures, especially in somatic stem cells in which the aberration ranges from 10-15% of investigated cells in human hematopoietic stem cells and 15-20% in human bone marrow-derived MSCs (hBM-MSCs) (20). Based on numerous reports, adult stem cells establish various chromosomal abnormalities within the 10 passages of in vitro expansion, however, independent laboratories have reported contrasting results in this regard (20). For instance, while Sense be and colleagues revealed that adult MSCs sustain a stable chromosomal integrity throughout long-term cultures (21), Ben-David and coworkers concluded from gene expression profiles that human adult MSC lines contain 4% of chromosomal abnormalities during in vitro expansion (22).…”
Section: Discussionmentioning
confidence: 99%